Identification of Therapeutic Targets in Autism Spectrum Disorder through CHD8-Notch Pathway Interaction Analysis. - Hewei Zhang; Shenghao Hua; Daiyan Jiao; Dong Chen; Qin Gu; Chao Bao (PLoS ONE)
Background Autism Spectrum Disorder (ASD) is a complex neurodevelopmental disorder with a rising global prevalence. Mutations in the CHD8 gene have been implicated in ASD, yet the underlying molecular mechanisms remain insufficiently understood. Methods We analyzed transcriptomic data from the CHD8A and CHD8B allelic deletion sample dataset GSE236993 to identify differentially expressed genes (DEGs). We intersected these DEGs with genes related to the Notch signaling pathway and performed functional enrichment analyses, including Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment, as well as protein-protein interaction (PPI) analyses, to identify key genes. These key genes were validated using the CHD8-deficient sample dataset GSE85417, resulting in the identification of seven common key genes. We then constructed drug-gene interaction networks and microRNA (miRNA) regulatory networks to further elucidate the mechanisms by which CHD8 impacts ASD. Results Seven hub genes-IGF2, FN1, CXCR4, COL11A1, ITGA6, LOX, and FBN2-were identified, all involved in the Notch signaling pathway and playing significant roles in neurodevelopment and extracellular matrix regulation. Among these, IGF2 and CXCR4 were particularly crucial in ASD pathogenesis, suggesting their potential as diagnostic biomarkers and therapeutic targets. MiRNA regulatory network analysis revealed several miRNAs that may modulate these hub genes, offering new insights into ASD pathogenesis. Drug-gene interaction analysis suggested possible therapeutic small-molecule compounds, such as AMD3100 and IGF-1R inhibitors. Conclusions Our multi-level bioinformatics analysis identified key genes and regulatory networks potentially involved in ASD associated with CHD8 deficiency. These findings enhance the understanding of ASD's molecular mechanisms and highlight potential therapeutic targets, paving the way for future diagnostic and treatment strategies.